2010
DOI: 10.1177/003335491012500212
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Lead Poisoning Risk Assessment Methods: Census Block Group Characteristics vs. Zip Codes as Predictors

Abstract: Our equation offers better specificity and sensitivity than using dichotomized zip codes and Medicaid status, thereby identifying more high-risk children while also offering substantial cost savings. Our prediction equation can be used with a simple Internet-based program that allows health-care providers to enter minimal information and determine whether a BLL test is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 32 publications
2
46
0
Order By: Relevance
“…20,[24][25][26][27] It is also associated with poverty. 22,[26][27][28][29][30] Neighborhoods with higher median household incomes and/or newer housing significantly protect children from elevated BLLs. 24,25,[27][28][29][30][31] Most recently, Moody et al 22 found that even in neighborhoods of the highest household incomes, black children were still significantly more at risk for lead poisoning than white children were in the Detroit Metropolitan Area (DMA).…”
Section: Introductionmentioning
confidence: 99%
“…20,[24][25][26][27] It is also associated with poverty. 22,[26][27][28][29][30] Neighborhoods with higher median household incomes and/or newer housing significantly protect children from elevated BLLs. 24,25,[27][28][29][30][31] Most recently, Moody et al 22 found that even in neighborhoods of the highest household incomes, black children were still significantly more at risk for lead poisoning than white children were in the Detroit Metropolitan Area (DMA).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of environmental risk factors and understanding of the distribution of the lead in the environment is important for health departments in better targeting at risk populations [6][7][8][9]. Ecological studies modeling risk factors are also valuable because they give insight to public health intervention strategies [10][11][12][13][14][15][16][17][18]. For ecological studies of childhood lead poisoning, one needs to identify sources of lead toxicity and determine environmental risk factors based on the distribution of the toxicants and how children come into contact with them in their daily lives [19][20][21][22][23][24][25][26][27][28].…”
Section: Ecological Studies and Gis Use In Childhood Lead Poisoningmentioning
confidence: 99%
“…Public health departments recognized the advantages of GIS in screening, exposure prediction, and mapping cases. Using BLL data for lead poisoning, an increasing number of GIS-based ecological studies have identified risk factors as socioeconomic status (SES) [9][10][11][12][13][14][15][16][17][18]21], year built of housing [7][8][9][10][11]13,[15][16][17][18]20,21,23,28], race [11,13,14,16,17,21,23,27,28] and ethnicity [15,16,18].…”
Section: Ecological Studies and Gis Use In Childhood Lead Poisoningmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research in Michigan 9 and elsewhere 10,11 has led to a refined geographic approach to predicting the BLL of children. Unlike previous studies that use ZIP codes and census tracts, this research relied heavily on the characteristics of the census-block group (the smallest geographic unit for which detailed data were available).…”
mentioning
confidence: 99%